2017
DOI: 10.4103/jrpp.jrpp_17_20
|View full text |Cite
|
Sign up to set email alerts
|

Training and validation of standardized patients for assessing communication and counseling skills of pharmacy students: A pilot study

Abstract: Objective:The objective of this study is to describe the process of training valid simulated patients (SPs) for assessing communication and counseling skills of pharmacy students’ performance.Methods:This is a cross-sectional and correlational study. Psychometric properties of checklist and SPs’ portrayals and their filling of the checklist regarding assessing pharmacy students were assessed. Five SPs who were working in the simulated patient's pool were volunteered to take part in the project, which one of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…The definition of communication used for this paper is the ability to communicate with patients, using effective verbal and nonverbal communication, considering patient's beliefs and attitudes, and delivering relevant information (Tindall et al, 1990;Kimberlin, 2006;Mafinejad et al, 2017). In this study, the term 'patient communication' includes emotional areas and skills such as empathy, social competency, and attitude.…”
Section: Patient Communicationmentioning
confidence: 99%
See 1 more Smart Citation
“…The definition of communication used for this paper is the ability to communicate with patients, using effective verbal and nonverbal communication, considering patient's beliefs and attitudes, and delivering relevant information (Tindall et al, 1990;Kimberlin, 2006;Mafinejad et al, 2017). In this study, the term 'patient communication' includes emotional areas and skills such as empathy, social competency, and attitude.…”
Section: Patient Communicationmentioning
confidence: 99%
“…), play a crucial role in fostering patient-medical staff relationships, therapeutic adherence, and improving therapeutic outcomes. Previous studies have noted that the outcome of an interaction between a patient and a pharmacist depends on the pharmacist's ability to use the correct communication and counselling skills (Shah & Chewning, 2006;Mafinejad et al, 2017). The Gaspar et al…”
Section: Introductionmentioning
confidence: 99%
“…The most commonly documented use of SPs in pharmacy curricula is for teaching and assessing interpersonal skills such as communication, motivational interviewing, and counseling skills, including the ability to show empathy during patient encounters 88,103–107 . Students may report improved confidence in their communication skills after interacting with SPs 86,108 .…”
Section: Standardized Patientsmentioning
confidence: 99%
“…89 The most commonly documented use of SPs in pharmacy curricula is for teaching and assessing interpersonal skills such as communication, motivational interviewing, and counseling skills, including the ability to show empathy during patient encounters. 88,[103][104][105][106][107] Students may report improved confidence in their communication skills after interacting with SPs. 86,108 In one study, mock patient interactions were more effective at teaching motivational interviewing skills to pharmacy students than peer role-play or written dialogue.…”
Section: Learning Outcomes Assessed Using Spsmentioning
confidence: 99%
“…This study suggested further training for simulated patients to standardize empathy ratings and improve inter-rater reliability. Trained simulated patients have been shown to act as consistent raters for communications skills [ 10 ]. The research question for our study was, whether trained simulated patients assessed medical students’ communication and interpersonal skills after physician-patient encounters from the internal perspective of the patient’s view (short: internal perspective) in the same way than from an external perspective of the patient’s view (short: external perspective) when rating the videographed interviews four months later.…”
Section: Introductionmentioning
confidence: 99%